Where does Campylobacter come from? A molecular odyssey - Cody, A; Colles, F; Sheppard, S; Maiden, M (Springer, 2009)
Campylobacter is the most common bacterial cause of gastroenteritis, worldwide. Since the first description of the disease in the 1970 s (Skirrow, 1977 the incidence of human campylobacteriosis in the UK, measured in terms of laboratory reports, has risen steadily, peaking at 57,674 reports in the year 2000; with 46,603 reports in 2006 (http://www.hpa.org.uk). Although generally self limiting, this disease has an important economic impact (Skirrow and Blaser, 1992). More serious complications, such as motor neurone paralysis, arise in 1–2 cases per 100,000 people in the UK and USA (Nachamkin et al., 1998). The disease also has an appreciable, yet less defined, impact in developing countries. Approximately 90% of human infection is caused by C. jejuni, with C. coli accounting for much of the rest (Gillespie et al., 2002).